2018
DOI: 10.1101/251181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic analysis with the progress of symbiosis in ‘crack-entry’ legumeArachis hypogaeahighlights its contrast with ‘infection thread’ adapted legumes

Abstract: 27In root-nodule symbiosis, rhizobial invasion and nodule organogenesis are host controlled. In

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Transcriptomic analysis is a powerful tool to reveal the interactions between host and pathogen [61][62][63][64]. In this study, we analyzed 35 pairs of samples from 69 pairs of Xooor Mor-infected rice microarray samples deposited in the GEO database.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis is a powerful tool to reveal the interactions between host and pathogen [61][62][63][64]. In this study, we analyzed 35 pairs of samples from 69 pairs of Xooor Mor-infected rice microarray samples deposited in the GEO database.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq data are downloaded from https : //www.ncbi.nlm.nih.gov/sra?term = SRP 107173 [6]. These data contain transcriptomic expressions of six root nodule developmental stages after the infection with Bradyrhizobium Semia 6144.…”
Section: Lncrnas Identification and Validationmentioning
confidence: 99%
“…Rhizobia enter through infection thread and root nodule primordium in these plants. As an exception, rhizobia directly invade root cortical cell via epidermal cracks in dalbergoid legumes like Arachis hypogaea [6]. Wild diploids parents of this plant are Arachis duranensis and Arachis ipaensis and their genomes are used for mapping purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some unresolved questions remain. One of them is that a recent transcriptome analysis in A. hypogaea failed to detect homologs of the Aeschynomene NCR genes ( Karmakar et al, 2018 ). However, this study identified another, small, family of cysteine-containing peptides, related to the antimicrobial PR-1 family and the authors suggested the involvement of these peptides in bacteroid differentiation.…”
Section: Nodule-specific Peptides Targeted To the Symbiosomementioning
confidence: 99%